Music, Leisure and Politics - Dimić, Zoran (Res Facta Nova, 2025)
Ancient philosophers were clearly concerned with the function of art (music, poetry, visual arts) in managing the political community. Philosophical consideration of the political foundations and function of music to form a public education is found in Plato (Republic, Laws) and Aristotle (Politics). Since we intend to make the relationship between music, leisure, and politics the central problem here, we pay the greatest attention to how Aristotle sees the connection between these concepts. Aristotle cares equally about preserving and nurturing all three functions of music in educating political community members. Therefore, he refuses to prioritize any of the functions of music because he considers all three functions necessary for the development of a happy member of the political community. In this article, we specifically stress the function of leisure. Its role in the political life of citizens in the best state constitution is to confirm citizens’ freedom. Namely, if the government in the polis does not work in the interest of all citizens and does not produce freedom for all, then it turns its citizens into slaves who spend their whole lives in hard work. The fact that legislators and politicians rule to produce enough leisure for their citizens is precisely the most significant proof that it is a government over free citizens and serves the interests of all, not just the one who rules. Leisure, that is, free time, actually constitutes the political being of a free citizen, to the same extent that the absence of leisure constitutes the political being of subjects and slaves in, for example, monarchy or tyranny. In the best constitution, it becomes crucial how the citizens spend their free time in leisure because a wrong choice would lead to their idleness. Hence, music becomes essential because, as Aristotle suggests, music and philosophy are good ways for citizens to practice their free political being.